EFEKTIVITAS MINYAK CENGKEH DAN PULPERYL® DALAM MENGHAMBAT AKUMULASI BAKTERI Streptococcus mutans SECARA IN VITRO - Hendri Poernomo; Mochammad Taha Ma'ruf; Setiawan Setiawan; PA Nindya Winda Wati (Interdental: Jurnal Kedokteran Gigi, 2018)
One of the complications that can occur after tooth extraction is dry socket. Bacterial infection is one among the various causes of dry socket where Streptococcus mutans become one of the bacteria that have a role as a cause. Eugenol is the main active substancethat owned by clove oil with eugenol as antibacterial properties. The research pyupose was to determine the effectiveness of clove oil in inhibiting the accumulation of Streptococcus mutans bacteria in the dry socket. The research method used to see the inhibition of clove oil 5% also the negative control of ethanol to Streptococcus mutans bacteria in the form of clear zone using a vernier caliper. The research result shows that the clove oil 5% effective in inhibiting Streptococcus mutans, with the average inhibition zone of clove oil 5% was 15 mm. Statistical test result showed significant results (ANOVA test = 0.001 with ρ <0.05). The conclusion that can be obtained from this study was clove oil 5%may inhibit the accumulation of Streptococcus mutans bacteria in the dry socket.